2019
DOI: 10.3389/fphar.2019.01433
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Salidroside on Cerebral Ischemia/Reperfusion-Induced Behavioral Impairment Involves the Dopaminergic System

Abstract: Salidroside, a phenylpropanoid glycoside, is the main bioactive component of Rhodiola rosea L. Salidroside has prominent anti-stroke effects in cerebral ischemia/reperfusion models. However, the underlying mechanisms of its actions are poorly understood. This study examined the anti-stroke effects of salidroside in middle cerebral artery occlusion (MCAO)-induced rat model of stroke and its potential mechanisms involving the dopaminergic system. Salidroside administration increased the levels of dopamine (DA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 70 publications
(83 reference statements)
0
38
0
Order By: Relevance
“…PI3K/Akt, p53, cyclin D1, caspase 3, bad, p55γ, BDNF, TrkB, GSK3β, CREB, claudin-5, NF-κB, HIF-1α (Hu et al, 2012;Song et al, 2012;Zhang et al, 2012;Chai et al, 2013;Zhang et al, 2016b; ( Chang et al, 2015;Chang et al, 2007;Ding et al, 2019;Xu et al, 2017;Yan et al, 2015;Yu, P. et al, 2017;Yu et al, 2016;Zhou et al, 2019) Daurisoline 5, 10, 20 mg/kg Cyt-C, Caspase 3, Caspase 9, SOD, MDA, GSH-Px (Li and Gong 2004;Yang et al, 2009 (Huang et al, 2018;Li et al, 2015;Lu et al, 2018;Xie, C. J. et al, 2018;Xu, N. et al, 2019) (Continued on following page) (Candelario-Jalil et al, 2007;Simao et al, 2012b;Wei et al, 2015;He et al, 2017;Koronowski et al, 2017;Yang et al, 2018b) Ellagic acid 10-100 mg/kg Bax, bcl 2, cyt C, caspase 3, PI3K/Akt, NOS, MDA, wnt/β-catenin, ZO-1, AQP 4, MMP-9 (Kaihua and Jiyu 2020;Liu, Z. B. et al, 2017;Nejad et al, 2015;Wang, F. et al, 2019) Glycoside Liu et al, 2018;Wei et al, 2017;Zhang X. et al, 2019;Zhong et al, 2019;Zuo et al, 2018) Iridoid glycoside Geniposide 5, 10, 20 mg/kg LDH, TNF-α, IL-1β, IL-6, IL-8, IL-18, NLRP3, ASC, caspase-1, raf/mek1/2/ erk1/2, MCP-1, ZO-1, occludin, Claudin-5, β-catenin, PI3K/Akt, Bcl-2/Bax, AchE, NOS, MDA, SOD (Fu et al, 2020;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3K/Akt, p53, cyclin D1, caspase 3, bad, p55γ, BDNF, TrkB, GSK3β, CREB, claudin-5, NF-κB, HIF-1α (Hu et al, 2012;Song et al, 2012;Zhang et al, 2012;Chai et al, 2013;Zhang et al, 2016b; ( Chang et al, 2015;Chang et al, 2007;Ding et al, 2019;Xu et al, 2017;Yan et al, 2015;Yu, P. et al, 2017;Yu et al, 2016;Zhou et al, 2019) Daurisoline 5, 10, 20 mg/kg Cyt-C, Caspase 3, Caspase 9, SOD, MDA, GSH-Px (Li and Gong 2004;Yang et al, 2009 (Huang et al, 2018;Li et al, 2015;Lu et al, 2018;Xie, C. J. et al, 2018;Xu, N. et al, 2019) (Continued on following page) (Candelario-Jalil et al, 2007;Simao et al, 2012b;Wei et al, 2015;He et al, 2017;Koronowski et al, 2017;Yang et al, 2018b) Ellagic acid 10-100 mg/kg Bax, bcl 2, cyt C, caspase 3, PI3K/Akt, NOS, MDA, wnt/β-catenin, ZO-1, AQP 4, MMP-9 (Kaihua and Jiyu 2020;Liu, Z. B. et al, 2017;Nejad et al, 2015;Wang, F. et al, 2019) Glycoside Liu et al, 2018;Wei et al, 2017;Zhang X. et al, 2019;Zhong et al, 2019;Zuo et al, 2018) Iridoid glycoside Geniposide 5, 10, 20 mg/kg LDH, TNF-α, IL-1β, IL-6, IL-8, IL-18, NLRP3, ASC, caspase-1, raf/mek1/2/ erk1/2, MCP-1, ZO-1, occludin, Claudin-5, β-catenin, PI3K/Akt, Bcl-2/Bax, AchE, NOS, MDA, SOD (Fu et al, 2020;…”
Section: Discussionmentioning
confidence: 99%
“…Many recent reports and reviews have highlighted that salidroside may exert anti-inflammatory, neuroprotective effects and improve cognitive function ( Li, M. et al, 2018 ; Xu, N. et al, 2019 ). Salidroside may involve the modulation of monoamine metabolism in the striatum and substantia nigra pars compacta (SNpc), which may be related to the function of the dopaminergic system in the cerebral I/R brain ( Zhong et al, 2019 ). Many studies reported salidroside protected against cerebral I/R injury via PI3K/Akt pathway, accompanying with Nrf2/NF-κB pathway ( Wei et al, 2017 ; Zhang, Y. et al, 2018 ; Zhang, J. et al, 2019 ; Zuo et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…After going through the remaining full-text articles, 120 articles were excluded for at least one of following reasons: 1) the article was not a research about ischemic stroke; 2) not an in vivo study; 3) the intervention was a combination of RRC with potential effect on ischemic stroke; 4) the study did not access the effects of RRC on the animal model of ischemic stroke; 5) no control group. Finally, 15 eligible studies (Chen et al, 2009; Shi et al, 2012;Chen et al, 2014;Yu et al, 2014;Han et al, 2015;Atochin et al, 2016;Chen et al, 2016;Liu et al, 2018;Zhang et al, 2018;Zuo et al, 2018;Zhong et al, 2019;Li et al, 2020;Zhang et al, 2020;Dong et al, 2021) involving 345 animals were identified (Figure 1).…”
Section: Study Inclusionmentioning
confidence: 99%
“…In traditional Russian (Siberian) folk medicine, Rhodiola rosea L. has been used as an adaptogenic medicinal product for a long time (Ioset et al, 2011), and the plant is useful for increasing mental and physical capacities (Panossian., et al, 2021). Modern pharmacological researchies have revealed multiple bioactivities from Rhodiola rosea L. and its components (RRC) such as anti-oxidative (Zhang et al, 2007), anti-inflammation (Pu et al, 2020), anti-fatigue (Shevtsov et al, 2003), immune enhancement (Tao et al, 2019) and neuroprotective effects (Yu et al, 2008), for treatment of Alzheimer's disease, cardiovascular disease, cognitive dysfunctions, cancer, and stroke (Zhong et al, 2019;Fan et al, 2020). Salidroside, rhodiosin, p-tryosol, pyridrde, rosavin, rhodionin (Zhang et al, 2006) and ferulic acid eicosyl ester (Michels et al, 2018) are the main bioactive compounds in the Rhodiola species.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic cerebral vascular disease can cause a different degree of neurological dysfunction and is considered to be a serious threat to public health for its high incidence, high morbidity, high disability, and high mortality characteristics ( Zhong et al, 2019 ; Cai et al, 2021 ). Cerebral ischemia-reperfusion (I/R) injury refers to the phenomenon that the cerebrum suffers from a permanent or transient ischemia and then suddenly restores the blood supply ( Block et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%